Enhanced moisture stability of perovskite photovoltaic with bifunctional molecule surface passivation - Teo, Teck Chye (2018)
With the growing need for renewable energy to replace fossil fuel in the near future, the advancement in the photovoltaic technology thus became the topic of interest. In particular, the inorganic - organic halide perovskite solar cells. Due to their excellent efficiency, they have revolutionise research in today’s photovoltaic technology. Although their PCE has reached over 20% in the recent years, their inherently poor environmental stability is a huge obstacle for practical usage. Herein, we introduce two strategies to improve the stability in perovskite cells. Firstly, is to tackle its moisture stability followed by reducing its surface recombination through passivation. 1H, 1H, 2H, and 2H-Perfluorooctanephosphonic acid as well as its salt compound is used as a surface passivation to improve moisture stability of inorganic – organic halide perovskite crystals, which also improves the overall perovskite solar cell stability. The hydrophobic property of the –CF group prevented water from penetrating the perovskite layer, enhancing its performance against humidity. From the XRD spectra, it can be seen that the presence of a hydrated intermediate (MA4PbI6∙2H2O); caused by the water molecule degrading the perovskite surface, is no longer present in the treated device after 30 days exposure in humid environment. The efficiency of the treated device was at least 80% of its original value after the exposure. The methylammonium group in the salt compound also successfully passivates the surface defect, reducing surface recombination by filling the MA vacancy on the perovskite surface. This project opens up the possibility of the use of various molecular additives into perovskite solution to surround grain boundary and passivate the defects. Highly stable inorganic – organic halide perovskite solar cells will definitely be possible in the near future.